Night Owl and Other Poems, With a Manifesto on Imagination and Poetics - Yuvarajan, Dushyandhan (Auckland University of Technology, 2016)
“The Night Owl and Other Poems” is a collection of poems that explores four areas of the human condition, destruction, humanity, sorrow and love, and explores how these four areas are affected under a variety of experiences and situations. Written during my travels throughout Asia and Europe, the collection uses the spectrum of my interactions during this time to interrogate the ideologies that motivate people’s actions in the world. The collection of poems is not penned in a particular style but erratically dances through a gamut of poetic forms and schools mirroring the turbulence of my emotions and their manifestations during this period. Each poem is spoken from the viewpoint of a different character, building on the concept that we all have multiple characters harbouring inside our minds, and each character is alive in different ways, leading to an often jarring juxtaposition of emotional tone between the works. Each section of the poetic manuscript relies heavily on abstract and surreal imagery. It transitions from sexual and destructive landscapes to internal and nature laden imagery and was heavily influenced by a combination of Beat poets, Romantic poets and Modern poets such as Allen Ginsberg, Seamus Heaney, Langston Hughes and Galway Kinnell. Supplementing the poetic collection is my philosophical manifesto exploring the unassailable relationship between human imagination and poetry through the application and analysis of objective procedural poetic techniques, where I argue that the human imagination is intrinsically married to poetry and the two cannot be divorced. It begins by laying out five explorative hypotheses to be tested. The philosophy then defines the term “objective procedural poetry” and explores the regions of the poetic sphere that have used or relied on this concept, untangling the history and complex relationship of subjectivity and objectivity in the composition of a poem. Following this, a variety of objective translational and non-translational transformations are applied on a range of my own poetry and that of others, after which I analyse and compare the outcomes to determine if a new self-standing artistic work has been derived or alternatively whether the original has been reimagined in a new artistic light. My philosophy then explores and dissects two specific areas of poetry, DADA and the “cut up”, and compares these techniques and their outcomes with the earlier results. Drawing on the extensive collection of examples, tests, results and analysis produced and conducted throughout the work, the philosophy concludes by affirming that the five hypothesis at the beginning of the philosophy have been adjudged true. Purely objective production of poetry does not result in artistic works, and thus every poetic work to a degree must be founded in the use of the subjective human imagination and condition.
Keywords: Poetry; Poetics; Imagination; Prose Poetry; Lyrical Poetry; Poetic Critique